2016
DOI: 10.3390/hydrology3010008
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Perceptions and Behaviors about Drinking Water in Australia and New Zealand: Is It Risky to Drink Water, When and Why?

Abstract: Consumers in most developed countries, including Australia and New Zealand, presume their drinking water is safe. How social perceptions about drinking water are formed, however, remains inadequately explored in the research literature. This research contributes exploratory insights by examining factors that affect consumer perceptions and behaviors. Individual perceptions of drinking water quality and actions undertaken to mitigate perceived risks were collected during 183 face-to-face interviews conducted at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 24 publications
(34 reference statements)
1
23
0
Order By: Relevance
“…However, as regard to streamflow management, the level of awareness and concern of the citizens was lower, indicating that citizens' interests are not directly aligned with managing flow rate. Additionally, some studies (Crampton & Ragusa, 2016;Gong et al, 2017) showed that improving the water quality of urban rivers indirectly influenced citizens' awareness of health. Notably, in urban areas, married individuals have a higher interest in improving water quality than do unmarried individuals because married respondents believe that streams with high water quality provide better recreational opportunities for their family than do streams with low water quality.…”
Section: Human Factors Affecting Water Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, as regard to streamflow management, the level of awareness and concern of the citizens was lower, indicating that citizens' interests are not directly aligned with managing flow rate. Additionally, some studies (Crampton & Ragusa, 2016;Gong et al, 2017) showed that improving the water quality of urban rivers indirectly influenced citizens' awareness of health. Notably, in urban areas, married individuals have a higher interest in improving water quality than do unmarried individuals because married respondents believe that streams with high water quality provide better recreational opportunities for their family than do streams with low water quality.…”
Section: Human Factors Affecting Water Qualitymentioning
confidence: 99%
“…Personal perceptions of streams can potentially influence river restoration policies and strategies that affect water quality changes (Chang et al, ; Lave, ). An individual's awareness of water resources may be closely associated with their personal demographic attributes (Crampton & Ragusa, ; Wohl et al, ). We anticipate that the perception of water resources is indirectly and directly related to changes in river water quality that could create feedback between the human and water systems (e.g., restoration efforts, policy changes, and so forth; Chen et al, ; Sivapalan & Blöschl, ).…”
Section: Introductionmentioning
confidence: 99%
“…Drawing on insights from critical media studies (Singleton et al 2006;Ragusa and Crampton 2016;Crampton and Ragusa 2016) and communication studies positing media presence may influence socioenvironmental campaigns (Day 2000), we questioned the coexistence of high media visibility and high awareness of environmental campaigns and low media visibility and unawareness, using the Internet and national newspapers as two popular mass communication modes. Findings showed high participation rates for Earth Hour and Clean Up Australia Day; moderate participation in Walk to Work Day, National Recycling Week, and World Environment Day; and low participation in Meat Free Week, Sustainable House Day, and Walk against Warming.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental campaigns, as key organizations promoting ES, are thus reliant on mass media who ensure compliance with corporatized norms, particularly not offending corporate sponsors, as well as journalists' and the public's overall low science literacy. Indeed, research reveals individuals' capacity to critically evaluate the quality of popularly presented scientific information is variable even among highly educated populations (Crampton and Ragusa 2016). Nevertheless, mass media have been found to play a major role in "revitalizing" public participation in environmental actions by "educating" and informing the public (Howarth 2012).…”
Section: Introductionmentioning
confidence: 99%
“…3 RESULTS AND DISCUSSION People's drinking water choices, in many ways, are based on municipal water community perception [36]. While studies exist on municipal water, groundwater and recycled water, limited resources were found on RHRW community perception, given recent government incentives to RHRW harvesting and use in Australia [37].…”
Section: Questionnaire Construction and Designmentioning
confidence: 99%